Deconstructing Ethical Ambiguity: Ethical Decision Making When Working With Multiple Ethical Codes of Conduct. Issue 2 (2nd July 2020) - Robinson, Jarryn; Moyer, Michael; Maghsoudi, Mahsa; Martinez-Smith, Cristina
ABSTRACT: Adherence to ethical standards is an ever-evolving topic in the counseling field. At different times throughout the educational and licensing processes, there are moments of ambiguity that can muddle professional judgment. Understanding ethical ambiguity as it occurs on a personal and systemic level is essential for the advancement of the profession. State mandated standards versus the American Counseling Association (ACA) ethical code, potentially create ethical dilemmas rooted in ambiguity of ideals. This article will deconstruct the ideology of ethical ambiguity as it exists within the Counseling field.